Penerapan Media Pembelajaran pada Materi Memformat Dokumen Pengolah Kata di SMK Negeri 17 Samarinda - Andi Rustandi; Muhammad Luthfi Anwar (UNDIKMA, 2021)
This study aims to analyze the feasibility of learning media on the subject of computer skills and information management based on the Google Classroom application for class X students majoring in Pharmacy at SMK Negeri 17 Samarinda. This research method uses a qualitative approach. Data collection techniques using questionnaires, interviews, observation, and documentation. The data analysis technique used in this research was qualitative and quantitative descriptive analysis.. The results of this study are: The feasibility of implementing Google Classroom learning media on the material for formatting word processing documents at SMK Negeri 17 Samarinda which has been tested for feasibility with the feasibility analysis technique using a Likert scale. based on an assessment by a media expert with a total score of 79 or 92.9% of the maximum total score so that it is in the very feasible category, an assessment by a material expert with a total score of 47 or 94% of the maximum score so that it is in the very feasible category, and an assessment by students with a mean total score of 63.5 or 84.67% of the total maximum score so that they fall into the very feasible category. Based on this assessment, it can be said that the application of Google Classroom learning media to the material for formatting word processing documents that will be applied to SMK Negeri 17 Samarinda is declared